Development of polyphenol-protein-polysaccharide ternary complexes as emulsifiers for nutraceutical emulsions: Impact on formation, stability, and bioaccessibility of β-carotene emulsions. (December 2016) - Liu, Fuguo; Ma, Cuicui; McClements, David Julian; Gao, Yanxiang
Abstract: The objective of this study was to design novel emulsifiers with the ability to improve the chemical and physical stability of nutraceutical emulsions. Ternary conjugates were fabricated by covalently bonding polyphenol, protein, and polysaccharide together. The protein was used to provide surface activity, the polysaccharide to provide strong steric repulsion, and the polyphenol to provide antioxidant activity. Chlorogenic acid (CA) was first grafted onto lactoferrin (LF) at pH 9.0, and then the CA-LF conjugate was attached to dextran (Dex) using the Maillard reaction. The resultant ternary conjugates were characterized by electrophoresis, mass spectrometry, and calorimetry (SDS-PAGE, MALDI–TOF–MS and DSC). The ternary conjugates exhibited better heat stability than the protein alone or binary CA-LF and LF-Dex conjugates. The utilization of ternary conjugates as emulsifiers in β-carotene-fortified emulsions was investigated under different processing and storage conditions. Ternary conjugates had better emulsifying properties than the protein alone or binary conjugates, and also led to β-carotene emulsions with improved physical and chemical stability. In particular, ternary conjugates were more effective at inhibiting β-carotene degradation induced by ultraviolet light exposure. Simulated gastrointestinal tract studies indicated that β-carotene was bioaccessible when encapsulated in emulsions stabilized by ternary conjugates. Graphical abstract: Highlights: Polyphenol-polysaccharide-protein conjugates were synthesized via an environmental-friendly method. The ternary conjugates were effective emulsifiers that could produce emulsions containing fine droplets. The ternary conjugates exhibited better physical and chemical stability than pure protein or binary conjugates. The bioaccessibility of β-carotene was scarcely affected by the ternary conjugates.